Metal‐Tellurium Batteries: A Rising Energy Storage System. Issue 2 (9th September 2020) - Chen, Ze; Zhao, Yuwei; Mo, Funian; Huang, Zhaodong; Li, Xinliang; Wang, Donghong; Liang, Guojing; Yang, Qi; Chen, Ao; Li, Qing; Ma, Longtao; Guo, Ying; et al.
Abstract : Tellurium (Te) is a member of the chalcogen family. Metal‐Te batteries have been explored in rising enthusiasm. Compared with sulfur (S) and selenium (Se), Te shows remarkable advantages, such as the higher electrical conductivity and better stability. The first report of metal‐Te battery was in 2014, and it has been deeply investigated due to its potential for next‐generation energy storage devices since then. Despite metal‐Te batteries are suffering from the same problems as metal‐S batteries, such as intermediates dissolution and large electrode volume change, the research direction can go in different ways due to new opportunities from Te. For instance, Te owns suitable redox potential, good conductivity, high volumetric capacity, and excellent stability, which makes it a strong candidate for negative electrode materials. This review attempts to summarize the current status of metal‐Te batteries and puts forward to some promising possibilities based on its short research history. As a rising energy storage system, the potential of Te‐based batteries in next‐generation high‐performance batteries deserves more attention and researches. Abstract : The current status and future potential of tellurium (Te)‐based batteries are reviewed. After providing a basis on metal‐Te batteries, related electrolytes in these systems, toxicity, and safety of Te and other application of Te in batteries are discussed. As future perspectives, aqueous Te batteries, Te anode, and other metal‐Te batteries are proposed.